Field reports, Beth Proescholdt, fall 1990 - Proescholdt, Bethet al (1990)
Field reports form with detailed notes explaining the form and sightings submitted by Beth Proescholdt for fall 1990. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1990. Epson - sheet feed